Survey on the Present Status of Infrastructure and Quality Management System in Golda Farms and Depots of Selected Area - Haider, MN; Faridullah, M; Islam, MN; Kamal, M (Progressive Agriculture, 2013)
Post harvest qualitative and quantitative changes have been studied in an important crustacean species prawn, Golda (Macrobrachium rosenbergii) of Bangladesh at various stages of handling Golda have been studied. Detailed information on post-harvest handling, storage, transportation, and distribution of prawn using pre-tested questionnaires was collected from some selected farms and depots of four Golda producing districts viz. Khulna, Bagerhat, Jessore and Norail area. The information on various aspects was collected through interview with cross section of people engaged in farms and depots. The aspects of information collected on Golda farms were: farm conditions, infrastructure, harvesting, farm production, post-harvest care, transportation and quality measures. Information collected on various aspects of depots was: infrastructure facilities, condition of shrimp during receiving, handling, transportation, washing and owners opinion about the quality of prawn from previous year experiences. The post-harvest losses of Golda is due to soft shell, improper washing or washing with unclean water, longer duration of harvesting, exposure of shrimp at high ambient temperature for a long time (delayed icing), contamination, piled up on a dirty floor, general lack of hygiene and dipping in water to weight gain was about 1-4% of the total harvested quantity. DOI: http://dx.doi.org/10.3329/pa.v19i2.16959 Progress. Agric. 19(2): 177 - 186, 2008